HUBUNGAN PENDIDIKAN KESEHATAN REPRODUKSI REMAJA DAN POLA ASUH ORANGTUA TERHADAP PERILAKU SEKS BEBAS PADA SISWA SISWI KELAS XII IPA SMA NEGERI 2 KOTA KUPANG - Marserli Rusanti Elimanafea (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2018)
Adolescence is a transitional period from childhood to adulthood with changes in secondary sex characteristics to sexual maturity and reproductive. Along with the primary and secondary growth of adolescence in the direction of perfect maturity, there is also an encouragement to channeling sexual desire. If teenagers do not get the right understanding and the role of good parenting from parents then teenagers will fall into free sex behavior. The purpose of this study was to determine the relationship of adolescent reproductive health education and parenting patterns toward free sex behavior in students of Class XII of SMA Negeri 2 Kupang. The research method used was correlation research with cross sectional approach. The Population in this study was the students of Class XII SMA Negeri 2 Kupang City of 315 students, sampling used Simple Random Sampling with the number of samples of 76 respondents. The results of the study stated that reproduction health education in Class XII students of SMA Negeri 2 Kota Kupang were in the relatively active category (53.9%), parenting pattern in the democratic category (52.6%) and free sex behavior in low risk category 65.8%). Chi Square test result stated that there was a significant correlation between reproduction health education and parenting pattern to free sex behavior with p value= 0,015, and p= 0,023 suggestion for society to implement reproduction health education and to apply appropriate parenting pattern for adolescent in order to prevent free sex behavior. Keywords: Reproduction Health Education, Parenting, Free Sex Behavior.